2001
DOI: 10.1176/appi.ps.52.12.1621
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a Barrier to Recovery: The Consequences of Stigma for the Self-Esteem of People With Mental Illnesses

Abstract: The stigma associated with mental illness harms the self-esteem of many people who have serious mental illnesses. An important consequence of reducing stigma would be to improve the self-esteem of people who have mental illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
645
3
29

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,023 publications
(728 citation statements)
references
References 17 publications
35
645
3
29
Order By: Relevance
“…Consistent with a widely ranging literature (Link et al, 2001;Wright et al, 2000), results revealed that among our sample the experience of greater levels of stigma was generally related to poorer self-esteem. Examining individual components of self-esteem using stepwise multiple regression equations controlling for response style, results suggest that participants who accepted stereotyped beliefs tended to view themselves as less competent and tended to have less moral self-approval.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with a widely ranging literature (Link et al, 2001;Wright et al, 2000), results revealed that among our sample the experience of greater levels of stigma was generally related to poorer self-esteem. Examining individual components of self-esteem using stepwise multiple regression equations controlling for response style, results suggest that participants who accepted stereotyped beliefs tended to view themselves as less competent and tended to have less moral self-approval.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, while identifying oneself as "a person with schizophrenia" may be linked to greater awareness of illness and possibly treatment adherence, it is also associated with threats to self-esteem, self efficacy and hope for the future (Link et al, 2001;Lysaker et al, in press;Lysaker et al, 2007a,b;Markowitz, 1998;Roe, 2003;Ritsher and Phelan, 2004;Wright et al, 2000;Watson et al, in press). In fact research has suggested that stigma may reduce self-esteem regardless of symptom level and cognitive function and lead to poorer outcome including depression, humiliation and shame (Birchwood et al, 2005;Landeen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the results are also consistent with research showing that levels of stigma change in association with treatment (31). Finally, the relationship between PDD and depression had already been established (7), and the current measures’ correlations with depression were comparable with those of the PDD. In fact, despite the statelike nature of depression, all four stigma measures demonstrated a stable relationship with the PHQ-9.…”
Section: Discussionsupporting
confidence: 66%
“…One study of over 80,000 participants across 16 countries concluded that perceived stigma is frequently and strongly associated with mental disorders worldwide (Alonso et al, 2008). Whether accurately interpreted or not, perceived stigma has been associated with negative outcomes when held by people with the stigmatizing attribute, including lower self-esteem; adherence to treatment; social adjustment and quality of life; and higher work, role, and social limitations (Alonso et al, 2009;Link, Struening, Neese-Todd, Asmussen, & Phelan, 2001;Perlick et al, 2001;Pyne et al, 2004;Sirey et al, 2001).…”
mentioning
confidence: 99%